PEMANFAATAN SUMBER BELAJAR (BAHAN & PERPUSTAKAAN) DALAM PEMBELAJARAN IPS KELAS VIII DI SMP NEGERI 24 SEMARANG TAHUN PELAJARAN 2014/2015 - Setiawan, Budi; -, Sutardji; -, Sriyanto (Edu Geography, 2016)
The quality of education closely related to the learning outcomes. Learning outcomes which are achieved by every student is different; high, medium, and low. Till now this learning process of Geography in grade of VIII SMP Negeri 24 Semarang still used teacher oriented strategy, where the teachers role as the primary learning source of knowledge. This study aims 1) To determine the utilization resource of student learning in social studies in class VIII SMP Negeri 24 Semarang, 2) To determine student learning outcomes in social studies class VIII in Chapter 7 of material social deviation, 3) To know the constraints of learning resources (Materials and Library) on learning social studies class VIII SMP Negeri 24 Semarang. Population in this research are students of class VIII A- VIII C SMP Negeri 24 Semarang totaling 97 students. Samples were students of class VIII B totaling 33 students. The results showed: 1). Class VIII B using a learning resource book author IPS package Sutarto et al, libraries, and the Internet 2). The average value of student learning outcomes of class VIII B has increased by 13.48 3). The constraints faced by the Book Package much less good condition, Many students who do not seek tasks over the Internet, and the library conditions were not conducive caused students are less excited to the Library.